Sprachliches Verhalten der polnischen Germanistikstudierenden am Beispiel vom Sprechakt „Einladen“ - Wolak, Agnieszka (Investigationes Linguisticae, 2011)
The aim of the paper is to present the variety of speech behavior of the Polish students of German Philology performing the speech act of inviting. Inviting is a specific speech act, which demands from L2-learners not only the knowledge of the language learned, but also the knowledge of speech behavior specific for the community which uses the language for everyday communication. The awareness of this fact has an influence on the speech behavior of L2-learners, which shows itself in the quality of utterances used.